Hubungan Pola Asuh Otoriter pada Masa Kanak-Kanak dan Kecerdasan Emosional terhadap Komunikasi pada Pernikahan - Cindy Aurellia Budiono; Jenny Lukito Setiawan (Universitas Airlangga, 2026)
Communication is an important factor in marriage; however, not all couples are able to maintain effective communication, even in long-term marriages. This study aims to examine the influence of authoritarian parenting in childhood and emotional intelligence on communication in marriages of more than 10 years. The method used is a quantitative correlational with 200 participants in East Java who have been married for at least 10 years. The instruments used were The Three Couples Scales (PREPARE/ENRICH), Parenting Styles and Dimension Questionnaire (PSDQ), and Wong and Law Emotional Intelligence (WLEIS). The results showed a significant effect overall; however, partially, only emotional intelligence had a significant effect, while authoritarian parenting did not. This indicates that emotional intelligence plays a greater role in marital communication.